DINAMIKA STATUS HARA LAHAN KERING MENGGUNAKAN TABUNG HARA BIOCHAR BERMIKORIZA - Harsani Harsani; Zulkifli Zulkifli; Muhammad Ikbal Putera (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2023)
T Soil is a home for some microorganisms and a place for plants to grow; it is also a provider of both micro and macronutrients. This study aimed to determine the nutrient status on dry land using biochar and mycorrhiza nutrient tubes. This research was carried out on moorland using descriptive quantitative research in three treatments: control (B0), biochar nutrient tubes (B1), biochar tubes + Mycorrhiza nutrients (B2). The variables observed in this study were soil chemical properties, including N, P, C-organic, and pH. The results of nutrient analysis after the application of biochar and mycorrhiza for 3 and 6 months showed that the nutrient tube + mycorrhiza treatment showed the best results on soil chemical properties parameters, namely c-organic, N, P, and soil pH..